Pathogen removal using saturated sand columns supplemented with hydrochar - Chung, J. W. (Jae Wook), 1980- (CRC Press, 2015)
Lack of clean water is one of the most important public health challenges in less developed communities. Due to insufficient financial and technical resources in places in need, development of low-cost water treatment technologies can play a key role in sustainable water provision.